The road to independence for Kosovo : a chronicle of the Ahtisaari plan / Henry H. Perritt, Jr. - Perritt, Henry H., Jr., 1944- (Cambridge University Press, 2010)
This book tells the story of Kosovo's independence, from the periodic bloodshed of the twentieth century to the diplomacy that led to a determination of Kosovo's final status as a state in 2008. Kosovo declared its independence from Serbia in February 2008, over the objection of Serbia and Russia. This culminated in more than a hundred years of, sometimes violent, resistance to what the majority Albanian population considered to be 'occupation' by foreign forces - first those of the Ottoman Empire, then those of Serbia, and finally by the United Nations. Kosovo's independence was the product of careful diplomacy, orchestrated by the United States and leading members of the European Union, under a framework brokered by former Finnish president Martti Ahtisaari, who subsequently won the Nobel Prize for Peace.